1997
DOI: 10.1088/0953-8984/9/14/010
|View full text |Cite
|
Sign up to set email alerts
|

A photoemission investigation of the valence band electronic structure of and

Abstract: The valence bands of the intermetallic compounds Pd 2 TiIn and Pd 2 TiSn have been investigated by ultraviolet photoemission utilizing synchrotron radiation. The valence bands of both alloys have a width of 7-8 eV with a prominent peak at a binding energy of 2.6 eV and a shoulder extending to the Fermi edge. Measurements obtained at the Pd 4d Cooper minimum and at the Ti 3p threshold indicate that the feature at 2.6 eV is largely composed of contributions from Pd 4d states, whereas the Ti 3d states contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Comparing these results with earlier photoemission measurements on Heusler alloys, it is apparent that the shape of the valence band of Co 2 MnSn is very similar to that of Ni 2 MnSb, 28 while the valence band of Pd 2 MnSn resembles that of Pd 2 TiSn. 29 The spectrum obtained for Cu 2 MnAl has been reported in an earlier paper 30 and is very similar to that obtained in a separate photoemission study using a He I (21.2 eV) source. 31 Investigating each alloy in more detail, the Co containing sample will be considered first.…”
Section: Resultssupporting
confidence: 83%
“…Comparing these results with earlier photoemission measurements on Heusler alloys, it is apparent that the shape of the valence band of Co 2 MnSn is very similar to that of Ni 2 MnSb, 28 while the valence band of Pd 2 MnSn resembles that of Pd 2 TiSn. 29 The spectrum obtained for Cu 2 MnAl has been reported in an earlier paper 30 and is very similar to that obtained in a separate photoemission study using a He I (21.2 eV) source. 31 Investigating each alloy in more detail, the Co containing sample will be considered first.…”
Section: Resultssupporting
confidence: 83%
“…The electronic structure of Pd 2 TiSn was discussed in detail in the previous papers [12][13][14] and we treat it as the reference system. The UPS measurements [15,16] showed that the density of states at the Fermi level consists of two contributions from Pd 4d and Ti 3d states. In the total DOS for Pd x TiSn below the Fermi level we observe three peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Using the ab initio LMTO method we try to give answer whether the cubic semi-Heusler PdTiSn alloy is a semiconductor or metal. The band structure of Pd 2 TiSn was investigated by ultraviolet photoemission spectroscopy (UPS) [15,16] and x-ray photoemission spectroscopy (XPS) [10,17]. The UPS measurements [15,16] have shown that the valence band extends to 7-8 eV below the Fermi level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angle integrated photoemission experiments for Pd 2 TiIn were reported by Brown and co-workers. [57] These measurements were carried out at different photon energies in order to separate the Pd and Ti contributions to the occupied electronic structure. They show a valence band width of slightly less than 6 eV, in very close accord with the calculations.…”
Section: -3mentioning
confidence: 99%